Worldwide production on sleep apnea from 2009–2018. Analysis of the ability to secure funding and international collaboration networks. (August 2021) - García-Rio, Francisco; Alonso-Arroyo, Adolfo; de-Granda-Orive, José Ignacio; Castelló-Cogollos, Lourdes; Aleixandre-Benavent, Rafael
Abstract: Background: Obstructive sleep apnea (OSA) is an emerging health problem, but information on scientific production in this subject area is scarce. We aim to evaluate the scientific production on OSA from 2009 to 2018 to illustrate its worldwide distribution, topic areas, and ability to secure funding, as well as to describe international collaboration networks in this field. Methods: Articles published between 2009 and 2018 were extracted from the Science Citation Index Expanded via Web of Science (WoS) using the search term "obstructive sleep apn*". Publication year, number and country of authors, journal, subject category, key words, funding source and number of citations received were recorded. We also conducted network analyses for key words and international collaboration. Results: 12, 666 articles on OSA were located, which had increased from 895 documents in 2009 to 1592 in 2018. The progressive growth in scientific production on OSA had outpaced the growth rate of total WoS production since 2012.50% of the articles declared some type of funding, with a citation index higher than manuscripts that were not funded. The manuscripts were distributed in journals from 135 subject categories of the WoS, and keyword distribution showed a dispersed pattern with a high number of nodes. The international collaboration rate was 18.2%, and the country network showed the United States as the hegemonic node. Conclusion: World production on OSA has grown at a higher rate than global production and shows notable thematic dispersion as well as a high ability to secure funding, which increases its impact. Highlights: This study evaluates the worldwide scientific production on obstructive sleep apnea (OSA) from 2009 to 2018 showing a growth rate higher than the overall scientific production rate, with a wide geographical distribution, great dispersion of subject areas and a remarkable capacity to secure funding, which results in greater bibliometric impact. Furthermore, the analysis manages to define the collaboration networks between authors from different countries